Effect of 'Kuat' a theory- and web-based health education intervention on mental health literacy among university students: a study protocol - Zulkiply, Siti Hafizah; Abdul Manaf, Rosliza; Dahlan, Rahima; Dapari, Rahmat (Public Library of Science, 2023)
Background Mental health problems, particularly depression and anxiety disorders are the leading causes of disease burden. Despite the effectiveness of mental healthcare services and the impairing effects of untreated mental health problems, the rate of help-seeking is low among young people. In addition, the mental health burden gap is high in low- and middle-income countries. Good mental health literacy has been associated with better help-seeking.